"Our Troubled Neighbour Across the River": Transborder Journalism in a Canadian–US Border Region. Issue 2 (3rd April 2017) - Grieves, Kevin
Abstract: Coverage of the city of Detroit's 2013 bankruptcy by international and national journalists has been criticized for its sensationalism and distortion. Journalists from Windsor, Ontario, just across the river, cover the Detroit story as simultaneously international and local news. Analysis of Windsor newspaper and broadcast content indicates general avoidance of those tendencies. Elements of strong transborder connectedness, but also complex and sometimes conflicted sentiments appear in professional journalistic narratives as well as in user comments on a humorous online news poll.